Organizational Culture as determinant of Work Commitment of School Teachers - Imtiaz, Dr. Nasheed (IJRDO- Journal of Educational Research, 2016)
In this modern challenging world, it is quite difficult for organizations to survive. Organizational modernity and work force utilization are becoming increasingly important for any emerging and growing organization. Hence, among all commitment of an employee is a hall mark for organizations to grow and develop and finally to sustain in the highly competitive global market. To attain maximum possible commitment of employee’s organizations must take care of those factors which play significant role in enhancing the commitment level. In view to the above assertion, organizational culture is one of the very important aspect which plays vital role for determining work commitment of employees at work. Hence, present investigation was undertaken to investigate the determining organizational culture for influencing employees work. The study comprised of N= 200 teachers who were taken from schools. The findings have suggested that organizational culture significantly influences work commitment.